ANALISIS EFEKTIVITAS PROGRAM CSR DALAM PEMBERDAYAAN MASYARAKAT DI TENGAH ERA DIGITALISASI - Nuursyifa Eka Putri; Ersi Sisdianto (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study explores the effectiveness of Corporate Social Responsibility (CSR) programs in strengthening communities amidst the development of the digital era. The purpose of this study is to assess the contribution of CSR programs to sustainable community development by integrating digital tools and strategies. Using both qualitative approaches, the study analyzed and identified key elements that are instrumental in leveraging digitalization tp empower communities. The findings highlight the barriers and oppurtunities companiesface in aligning CSR program with technological innovation to achieve long-term social impact. This research provides valuable inshights for companies and policy makers to optimize CSR strategies in digital era.